The Use of Problem-Based Learning Model Assisted by Quizizz to Improve The Mathematical Problem-Solving Ability of Junior High School Students - Naila Naswa Fazliana; Dahlia Fisher; Jusep Saputra (Universitas Suryakancana, 2026)
This study aims to determine whether the mathematical problem-solving ability of students who receive the Problem-based Learning model assisted by Quizizz is better than students who receive the conventional learning model. This study uses a quantitative approach with a quasi-experimental design. The subjects of this study consisted of two classes, namely class VIII D as the experimental class that received the Problem-based Learning model assisted by Quizizz, and class VIII C as the control class that received the conventional model in one of the state junior high schools in West Bandung district. The instrument used in this study was a test of mathematical problem-solving ability. The data analysis technique for the mathematical problem-solving ability test used a two-sample test (t-test), which was processed using the IBM SPSS Statistics 23 for Windows software. The study's results showed that the mathematical problem-solving ability of students who received the Problem-based Learning model, assisted by Quizizz, was better than that of students who received the conventional learning model.